STRATEGI KOMUNIKASI PEMASARAN TERPADU (IMC) UNTUK MEMPERKUAT POSITIONING COKELAT LOKAL PREMIUM: STUDI KASUS TERVE CHOCOLATE DALAM MENJANGKAU HIGH SPENDING DAN LOYAL - Kezia Naomi Christy Ginting (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study is formulate an integrated marketing communications (IMC) strategy to strengthen Terve Chocolate’s positioning as a premium local chocolate targeted at consumers who wish to give elegantly and to savour personal moments with an authentic flavour. Terve has hitherto served selective, loyal and digitally adaptive consumers, but has not fully reached the premium consumer segment with high purchasing power and strong brand loyalty. Therefore, a communication strategy is required that integrates the product’s advantages with the emotional experience and exclusive value expected by this segment. The study uses a mixed-methods approach, with data collected through a survey of 265 respondents and in-depth interviews with 10 informants. Quantitative analysis was conducted using K-means clustering to identify market segmentation, while qualitative analysis employed content analysis techniques to explore consumer perceptions and experiences. The theoretical foundation comprises the STP framework, the 7P marketing mix, the Value Proposition Canvas, and an Integrated Marketing Communication (IMC) framework that are validated both practically and theoretically. The results of the study found that an IMC strategy based on storytelling, limited-edition product launches, collaborations with public figures, and multisensory experiences is capable of generating differentiation and loyalty among premium consumers. The implementation of this strategy also strengthens the brand image as a symbol of lifestyle and a provider of personal meaning. Principal recommendations include reinforcing the unique selling proposition (USP), integrating communication channels, and aligning brand messaging with the emotional values relevant to the premium segment.